IMPLEMENTASI PERATURAN MENTERI HUKUM DAN HAM RI NOMOR 16 TAHUN 2014 TENTANG TATA CARA PENGELOLAAN BENDA SITAAN DAN BARANG RAMPASAN NEGARA DI RUPBASAN SAMARINDA - Yogi Satria Nugraha (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT Purpose of this study to knew clearly about management procedures of confiscated objects and confiscated goods at RUPBASAN Samarinda. This study a kind descriptive study and include normative and empiric study. Location of this study at RUPBASAN Samarinda. Based of this result of study, it can be conclude that implementation mechanism of management confiscated objects and confiscated goods regulated in regulation of minister of law and human rights number 16, 2014 Keywords:  Management, Confiscated Objects, Confiscated Goods